Cyanide traces in coffee mystery of wayan mirna salihin's death - Diu, Raimun M. Yunus (Journal of Law Science, 2025)
The legal evidence procedure in the Wayan Mirna Salihin murder case, involving Jessica Kumala Wongso, is examined in this paper. Cyanide content is the key evidence. The research evaluates the validity and robustness of scientific evidence, specifically toxicological analysis, and how it is incorporated into the Indonesian criminal justice system using normative legal methodologies with descriptive-analytical and juridical-empirical approaches. The study data comprises legislation, court papers, and secondary legal information from scientific publications and journals. Results of the research show that cyanide levels in coffee is important to confirming murder. CCTV video, toxicological expert testimony, and motivation analysis convinced the court that Jessica mixed cyanide. The defense team questioned the laboratory test procedure and the absence of direct witnesses, casting doubt on this evidence. The Indonesian court system uses scientific and circumstantial evidence, yet popular opinion and controversy still affect justice views. Jessica was sentenced to 20 years in jail. This research concludes that Indonesia's legal evidence system needs improvement, particularly in scientific evidence management and proof criteria. Improvements to judicial openness and forensic competence are suggested to achieve substantive justice in difficult instances.